Uncertainty quantification in the Nuclear Data Program. (5th February 2015) - Brown, D A; Herman, M; Hoblit, S; McCutchan, E A; Nobre, G P A; Pritychenko, B; Sonzogni, A A
Abstract: The US Nuclear Data Program is charged with collecting, analyzing and archiving information critical to basic nuclear research and to the development of nuclear technologies. Users of nuclear data require detailed uncertainty information for a variety of reasons. In this paper, we review some of the main aspects of the generation and use of uncertainty information, linking to structure, astrophysics, and reaction data.